Usability Study Of Websites From The Perspective Of Student Internet Users - Jeyakuma, Robert (2005)
In the electronic commerce (EC) environment, a website projects the company's image to the world. Most existing studies, however, are focused on design guidelines for general Web users and unsupported by empirical findings. This study, therefore, carried out an empirical research on the usability of websites are perceived by a specific user group, i.e. Student Internet Users(SIUs).